Uma proposta de dashboard de métricas e indicadores para startups e incubadora tecnológica de Pato Branco - Ferreira, Rozimery (2022)
Data generated by business processes, especially in large software development companies, are important elements to be used to support decision making, which are based on indicators generated from metrics. On the other hand, both the incubator and the software startups have even more need to employ metrics to make the right decisions amid arrivals and limited resources. The reality is that many of these companies do not use their metrics, mainly due to lack of knowledge on how to obtain and apply them, or even for lack of an effective tool for generating adequate indicators. In this way, this work carried out in partnership with the Technology Incubator of Pato Branco (ITECPB) together with the incubated software startups, aims to identify, analyze and propose appropriate metrics and indicators for this public, in order to implement a dashboard for transformation and visualization of necessary indicators for decision making. The selection of metrics to be used was based on a bibliographical research and comparison with the methodologies already used by incubators and incubated. This information was collected through a diagnosis, in the form of interviews with ITECPB managers and incubated. After this stage, the project of a management dashboard for the incubator was developed, which was based on the Reference Center for Support to New Enterprises (CERNE) - level 1, and a dashboard prototype for the incubated ones. Both were developed using the Power BI tool and Python programming language. During the development of the dashboards, meetings were held to identify requirements and validate them. The delivery of the projects to the incubator was carried out in a meeting for presentation, explanation of use and sending of source codes and tutorial. The tools were very well received, with emphasis on the dashboard aimed at the management of the incubator, which already has streamlined and facilitated processes in the internal management and monitoring of the incubated, presenting positive points in relation to the visualization, access and sharing of information. The incubated dashboard was also presented and the startups attracted interest in its usefulness, however, it is still in the prototype phase and its complete development will be a future work.